Contribution of cattle farms towards river contamination with Giardia cysts and Cryptosporidium oocysts in Sungai Langat Basin - Farizawati, S.; Lim, Yvonne Ai Lian; Ahmad, R.A.; Fatimah, C.; Siti-Nor, Y. (Malaysian Society of Parasitology and Tropical Medicine, 2005)
A study to determine the contribution of Giardia cysts and Cryptosporidium oocysts from cattle farms was carried out at the Langat Basin. This study investigated the contribution of cattle farms, located near Sungai Langat and Sungai Semenyih, towards river contamination with these cysts and oocysts. The findings showed that out of 24 samples of water taken from Sungai Semenyih, 4.2% was positive for Giardia cysts with a concentration of 1.3 cysts/L and 20.8% were positive with Cryptosporidium oocysts with a range of 0.7 - 2.7 oocysts/L. At Sungai Langat, from the 43 samples taken, 23.3% were positive for Giardia cysts with a range of 1.5 - 9 cysts/L whereas 11.6% were positive with Cryptosporidium oocysts with a range of 2.5 - 240 oocysts/L. Isolation of cysts and oocysts in bovine faecal materials revealed that 14.6% of faecal samples were positive for Giardia cysts which had a range of 75 - 1.3x104 cysts/g and 25% were positive for Cryptosporidium oocysts with a range of 50 - 3.9x105 oocysts/g. From the cattle wastewater, 98% were positive with oocysts and 6.7% with cysts. The concentrations were between 20 - 3.1x103 oocysts/mL for Cryptosporidium and 4 - 75 cysts/mL for Giardia. Given that the prevalence of Cryptosporidium and Giardia are high amongst the cattle and the positive findings of the (oo)cysts in the river samples, it could be deduced that there is a very high possibility of the cattle farms contaminating the river with Giardia cysts and Cryptosporidium oocysts. Viability study of Cryptosporidium oocysts in the surrounding soil and pond within the cattle farm showed that the viability of Cryptosporidium oocysts decreased with time. It was estimated that it will take 52 days for all the oocysts from both environment to be non-viable. With a viability rate of approximately 2 months in a cattle farm setup, river water contaminated with Cryptosporidium oocysts has a high chance of acting as an agent of transmission. As cattle farms are also inhabited by the owners and their families, this problem may pose a threat to humans (e.g. children) especially if they are dependent on the river water as their source of water for their daily activities.